2012
DOI: 10.1136/annrheumdis-2011-201003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between area-level socio-economic deprivation and autoantibody status in patients with rheumatoid arthritis: multicentre cross-sectional study

Abstract: Among patients with RA, deprivation predicted RF positivity but not ACPA positivity. The effect of deprivation did not appear to be explained by smoking. Deprivation may be a marker for previously unrecognised, potentially modifiable environmental influences on the immunological phenotype of RA. Furthermore, given the known associations of RF positivity with prognosis and response to treatment in RA, these findings have potential implications for resource allocation and healthcare delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Our study is suggestive of a higher risk of RA in subjects with high SES. Findings regarding the risk of developing RA in relation to SES have not been uniform in the past 33,34,35,36 . There are some characteristics in this population that may be related to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is suggestive of a higher risk of RA in subjects with high SES. Findings regarding the risk of developing RA in relation to SES have not been uniform in the past 33,34,35,36 . There are some characteristics in this population that may be related to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic status (SES) also exerts influence on RA disease outcomes; those with lower SES have higher rates of comorbid disease (9). Current data reinforce the regional and sociocultural impact on clinical health outcomes, with identification of area level and personal factors that independently affect outcomes and interact to amplify the effect (10,11). The confluence of previously poorly described factors, such as residence, comorbidity, and access to care, has a significant impact on clinical outcomes and contributes to the overall burden of RA disease.…”
Section: Introductionmentioning
confidence: 86%
“…Additionally, since the two studies only assessed the RA prevalence trend before 2014, the trend after that remained unknown. Other relevant research has suggested that high socioeconomic status (SES) is significantly associated with a lower risk of developing RA [ 9 ], so a better understanding and management of SES may result in preventing the onset of RA [ 10 ]. However, studies that examined the RA prevalence trend in different SES situations have been rare in the last decade.…”
Section: Introductionmentioning
confidence: 99%